Long-Term Visual Outcomes in Infectious and Non-Infectious Uveitis: A Systematic Review - Nabila Maharani Ahmadi Putri; Christie July Prawatya (Journal of Language and Health, 2025)
Uveitis is a heterogeneous group of intraocular inflammatory diseases and remains a significant cause of long-term visual impairment in both pediatric and adult populations. Visual outcomes vary widely depending on disease etiology and the development of vision-threatening ocular complications. This systematic review aimed to compare long-term visual outcomes and ocular complications in patients with infectious and non-infectious uveitis. A systematic literature search was conducted in PubMed, the Cochrane Library, Scopus, Google Scholar, and PROSPERO for studies published between January 2015 and 2025, in accordance with PRISMA 2020 guidelines. A total of 847 records were identified55 duplicates were removed, 792 records were screened, 49 full-text articles were assessed for eligibility and 14 studies were included in the qualitative synthesis. Eligible studies included pediatric and adult patients with anterior, intermediate, posterior, or panuveitis reporting at least one long-term visual outcome, including best-corrected visual acuity (BCVA), severe visual impairment or blindness, or vision-threatening ocular complications. Study selection and data extraction were performed independently by two reviewers. Due to substantial heterogeneity, findings were synthesized using a qualitative narrative approach. Fourteen studies met the inclusion criteria. Non-infectious uveitis was more frequently reported than infectious uveitis across included studies. Long-term visual outcomes were commonly reported using BCVA measures, and cataract, glaucoma or ocular hypertension, and macular complications were the most frequently described long-term sequelae in both etiologic groups. Direct quantitative comparisons were limited by heterogeneity in study design, outcome definitions, and follow-up duration. Long-term visual outcomes in uveitis vary by etiology and are frequently influenced by vision-threatening complications. These findings highlight the importance of accurate etiologic classification and long-term follow-up in both pediatric and adult patients to reduce visual morbidity.